Requirements uncertainty propagation in conceptual design using bayesian networks - Spinelli, Andrea; Sharma, Ankit; Kipouros, Timoleon (International Council of the Aeronautical Sciences (ICAS), 2024)
This paper presents the application of a Bayesian Network as a tool for propagating the uncertainty between the aircraft-level design and the component-level design. The framework is applied to an example case in UAV design for payload transport. By querying the model, we demonstrate its ability to capture the casual relationships of the design problem and propagating the effects of design decisions on other parameters and requirements.
Keywords: Requirements uncertainty; Machine learning; Bayesian networks; UAV Conceptual design